The Social and Economic Roots of the Scientific Revolution Texts by Boris Hessen and Henryk Grossmann - Freudenthal, Gideon; McLaughlin, Peter (Boston Studies in the Philosophy and History of Science, 2009)
The texts of Boris Hessen and Henryk Grossmann assembled in this volume are important contributions to the historiography of the Scienti?c Revolution and to the methodology of the historiography of science. They are of course also historical documents, not only testifying to Marxist discourse of the time but also illustrating typical European fates in the ?rst half of the twentieth century. Hessen was born a Jewish subject of the Russian Czar in the Ukraine, participated in the October Revolution and was executed in the Soviet Union at the beginning of the purges. Grossmann was born a Jewish subject of the Austro-Hungarian Kaiser in Poland and served as an Austrian of?cer in the First World War; afterwards he was forced to return to Poland and then because of his revolutionary political activities to emigrate to Germany; with the rise to power of the Nazis he had to ?ee to France and then Americawhilehisfamily,whichremainedinEurope,perishedinNaziconcentration camps. Our own acquaintance with the work of these two authors is also indebted to historical context (under incomparably more fortunate circumstances): the revival of Marxist scholarship in Europe in the wake of the student movement and the p- fessionalization of history of science on the Continent. We hope that under the again very different conditions of the early twenty-?rst century these texts will contribute to the further development of a philosophically informed socio-historical approach to the study of science.